The Construction, Sources, and Implications of Consensualism in Contract Lesson from France - Abry, Kane. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book offers a comprehensive introduction to French contract law with a focus on the role of consent and the evolution of consensualism, considering its immediate historical sources. The book provides a clear, in-depth, and analytical discussion of the contingency of consensualism and how the development of consensual ideas across time and transnational geographical settings has specifically underpinned modern French contract law, which has inspired other legal systems and continues to do so. It also challenges the macro-narratives of European legal history and redefines consensualism so that it may be properly understood, addressing its manifest contemporary misinterpretations. Thorough, engaging, well-structured and inventive, there is no other English-language scholarly work that offers a similar analysis. "This monograph makes an evident contribution to the field by offering an original interpretation of several provisions in the Code Civil which relate to the law of contract. The author demonstrates an impressive grasp of Latin, French and English sources as well as knowledge of Roman law, legal history, and contemporary French law. It is well-referenced and offers an extensive bibliography". - Dr Stephen Bogle, Senior Lecturer in Private Law, University of Glasgow, UK "The author brings a critical perspective to bear throughout the monograph and develops a clear and quite sophisticated position on the interaction between consensualism and formalism in Roman and French law and the intervening European ius commune". - Prof Hector MacQueen, Emeritus Professor of Private Law, University of Edinburgh, UK.
Introduction -- PART I. IDEA AND ROLE OF CONSENT IN THE DEVELOPMENT OF A TAXONOMY OF CONTRACT IN ANCIENT LAW -- Roman law -- Mos gallicus and iuris Franco-Gallici -- Modern law -- RECEPTION, RELEVANCE, EVOLUTION, AND IMPLICATIONS IN THE CIVIL CODE OF FRANCE: DE LEGE LATA -- Article 1108 et seq. and the specification of the consensual doctrine -- PART III. RETHINKING THE FRENCH PERSPECTIVES ON CONSENSUALISM: DE LEGE FERENDA -- Articles 1109 and 1172, and the classification of contracts: Problems and perspective -- Reconsidering consensualism and the role of consent in contract -- Conclusion.
Keywords: Law -- Philosophy; Law -- History; Theories of Law, Philosophy of Law, Legal History